Pengembangan Sistem Array dalam Menentukan Nilai Rata-Rata Tinggi Badan - Marlina, Leni (PT The Collaboration UVW, 2023)
Technology that is increasingly sophisticated and continues to be developed with a variety of existing knowledge can easily help human work. The use of this technology can be applied in data management on a large scale, if calculated with manual capabilities it will take a long time to complete. This study aims to help process data on a large scale so that with the help of Del C++ program technology using Array language this kind of problem can be easily solved. Array programming language is a programming language that uses different indexes but the data type is the same. This program functions in determining the average value of an array. data or often referred to as Mean. Mean is the sum of all data and divided by a lot of existing data so that the median or average value of a data is obtained. Many agencies require this programming, especially health installations and educational institutions that are very requires an average component in order to calculate the average height of patients and students whose data is on a large scale so that it is difficult to calculate manually. The use of this program is considered more effective in processing data and finding the middle value of existing data so that objective data is obtained. if it is observed by going directly into the field so that there are no presumptions or prejudices that arise from the data obtained and it is efficient in determining what the mean value.